2017
DOI: 10.1111/1468-2427.12468
|View full text |Cite
|
Sign up to set email alerts
|

Idioms of Accumulation: Corporate Accumulation by Dispossession in Urban Zimbabwe

Abstract: David Harvey's notion of ‘accumulation by dispossession' has inspired a wide range of studies in different places. But it has hardly registered in the area of urban land grabbing in Africa and what the role of local capital has been in these processes. In this article, I use archival data, field observations and insights from key informant interviews in Harare to examine how the 1990s neoliberalism and the post‐1999 Zimbabwe crisis created new opportunities for accumulation of wealth through the irregular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…: 64). At the urban scale, accumulation by dispossession has been observed from processes of gentrification and displacement (Smith, ; Shin, ; Lees, ), the transfer of public land into private hands (Mbiba, ), ‘new urban enclosures’ in housing commodification and regeneration (Hodkinson, ), as well as revanchist practices that separate citizens from their urban commons such as the policing of public space and the eviction of squatters (Smith, ; Gillespie, ).…”
Section: Theorizing Dispossessionmentioning
confidence: 99%
See 1 more Smart Citation
“…: 64). At the urban scale, accumulation by dispossession has been observed from processes of gentrification and displacement (Smith, ; Shin, ; Lees, ), the transfer of public land into private hands (Mbiba, ), ‘new urban enclosures’ in housing commodification and regeneration (Hodkinson, ), as well as revanchist practices that separate citizens from their urban commons such as the policing of public space and the eviction of squatters (Smith, ; Gillespie, ).…”
Section: Theorizing Dispossessionmentioning
confidence: 99%
“…Drawing on the notion of ‘value grabbing’ (Andreucci et al ., ), it is shown that the unequal distribution of value appropriated from land amongst the classes of actors involved in land development provides the basis for a new kind of contentious politics. In theorizing the new mechanisms by which accumulation by dispossession is unfolding on the fringes of Chinese cities, this article seeks both to deepen understandings of land politics and accumulation strategies in contemporary China and to contribute to the literature on urbanization and dispossession in the global South (Levien, ; Gillespie, ; Shin, ; Mbiba, ; Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…His work has helped respond to calls for political economy insights into why public institutions in African cities lack capacity and fail to capture land and property values (Monkham and Moore ; Palmer and Berrisford ; Turok ). It emphasises the heightened importance of urban land and property as bases for accumulation in Africa, where urbanisation is occurring without concurrent industrialisation (Goodfellow ; Pitcher ; on Harare, see Chirisa et al ; Mbiba ; Muchadenyika ). But in Harare—and elsewhere—urban patronage economies are not just about capturing land values, but are also about capturing votes (on “votebank” politics in South Asia, see Bayat ; Roy ; on Harare, see Muchadenyika ).…”
Section: Frontiers and African Citiesmentioning
confidence: 99%
“…The emergence of substantial informal settlements on Harare’s edge is particularly revealing of broader shifts in Zimbabwean statecraft because the country was previously notorious for its exceptionally strong postcolonial urban planning tradition (Kamete , , ; Mbiba ; Muchadenyika and Williams ; Potts ; Rakodi ). The scale of Harare’s new informal settlements could easily reach 500,000 people, in a city officially said to number between 1.5 million (Harare Urban) and 2.1 million (Greater Harare), providing evidence that may counter prior views that the city was stagnating (Mbiba ) .…”
Section: Harare’s Periphery 2000–2013: Party/state Production Of Unrementioning
confidence: 99%
See 1 more Smart Citation